Effect of Peripartum Nutritional Supplementation on Plasma Profiles of Macro Minerals and Postpartum Fertility in Jaffarabadi Buffaloes - Vala, KB; Dhami, AJ; Kavani, FS; Parmar, SC; Pathan, MM (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This investigation was undertaken on 40 transitional Jaffarabadi buffaloes with the objective to evaluate the effect of peripartum nutritional (multiminerals and bypass fat) supplementation without and with micro-minerals (Inj. Stimvet) and oral ecbolic (Boli Exapar) on uterine involution and postpartum fertility including plasma minerals profile. The animals of treatment group (n=20) received additional oral supplements daily with 50 g of chelated mineral mixture and 150 g of bypass fat along with concentrates for 6 weeks prepartum and 2 weeks postpartum over the control farm fed group (n=20). Ten buffaloes in each control and treatment group further received Inj. Stimvet 5 ml (micro-minerals) around day 45 prepartum and on day of calving. Half of these Stimvet treated and control subgroups also received Exapar (n=5) 2 boli/day for 4 consecutive days postpartum. Blood samples were obtained on day –45, –30, –7 and 0 (day of calving), 7, 15, 30, 45, 60 peripartum for estimation of minerals profile. Animals were followed for puerperal events, uterine involution and intervals for postpartum first estrus and conception. The feeding of bypass fat and chelated minerals had significant effect on the time required for expulsion of placenta (3.93±0.24 vs 7.18±0.72 hrs; p<0.01), uterine involution (32.75±0.57 vs 37.00±0.56 days; p<0.05), intervals for first estrus postpartum (79.05±3.82 vs 100.55±3.47 days; p<0.05) and service period (107.10±4.43 vs 133.65±6.04 days; p<0.05). The prepartum mean plasma calcium and inorganic phosphorus levels in the buffaloes of both control and treatment groups decreased significantly on the day of calving, and then gradually increased during the days postpartum, again reaching at par with prepartum levels at around day 15-30 postpartum. The mean plasma calcium levels were observed to be higher in treatment than control group at most of the intervals. The mean plasma inorganic phosphorus values on periods closer to calving were apparently higher in treatment group than the control group. Further, the levels during close peripartum period were observed to be apparently higher in untreated subgroup as compared to Stimvet and Exapar alone or its combination subgroups. The mean plasma magnesium concentrations were found to be almost consistent during entire peripartum period studied in both the groups with apparently higher values in treatment than control group at most of the intervals. Very similar trend was also found in subgroups treated with Stimvet and oral Exapar alone or in combination, being little higher in Stimvet injected subgroup